2015
DOI: 10.1638/2012-0212.1
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance in Wild Bird Populations: Importance of the Food Chain

Abstract: The presence of multidrug-resistant (MDR) Escherichia coli has recently been reported in wild birds (gulls and birds of prey) that had no apparent exposure to antimicrobials. Little work has been done to assess the role of the food chain in the emergence and spread of MDR E. coli . In this study, we evaluated the presence of MDR E. coli in 29 fecal samples collected from wild birds living in a rehabilitation center (the center receives injured animals found in their natural habitat) and in eight feed samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The environment is the major harbour for antibiotic resistance, where they hold antibiotic residues which contributes for the development of resistance by selection pressure 14 . The irrational and inappropriate usage of antibiotics in veterinary and agriculture fields has led to the emergence and diffusion of resistance in bacteria derived from food-producing animals 15,16 . In particular, the emergence of antibiotic resistance in environment and microflora of food producing animals are of great concern due to the risk of getting entry into the food chain and can transmit to people and animals 14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environment is the major harbour for antibiotic resistance, where they hold antibiotic residues which contributes for the development of resistance by selection pressure 14 . The irrational and inappropriate usage of antibiotics in veterinary and agriculture fields has led to the emergence and diffusion of resistance in bacteria derived from food-producing animals 15,16 . In particular, the emergence of antibiotic resistance in environment and microflora of food producing animals are of great concern due to the risk of getting entry into the food chain and can transmit to people and animals 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…The irrational and inappropriate usage of antibiotics in veterinary and agriculture fields has led to the emergence and diffusion of resistance in bacteria derived from food-producing animals 15,16 . In particular, the emergence of antibiotic resistance in environment and microflora of food producing animals are of great concern due to the risk of getting entry into the food chain and can transmit to people and animals 14,15 . Hence the present study was designed to screen for antibiotic resistance E. coli from the environment (sewage) and the animal food sectors (piggery, poultry, cattle farms).…”
Section: Discussionmentioning
confidence: 99%
“…The intake of water polluted with faeces or human waste and the acquisition via food seem to be the sources of transmission of resistant bacteria of human and veterinary origin to wild birds (Reed et al 2003;Pindi et al 2013;Pinto et al 2015). Birds not only acquire pathogens from the environment, but also return them via excretion, potentially facilitating the dissemination of pathogenic organisms to both humans and other animals, especially through water (Benskin et al 2009;Wellington et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Of the sample of articles discussed in this subsection, a small number of studies reported how isolates with intermediate susceptibility were handled. Two studies retained such isolates as intermediates (Shobrak and Abo-Amer, 2014;Vidal et al, 2017), another reclassified the isolates as susceptible (Pinto et al, 2015), and in our previous work we classified all intermediates as resistant (Vogt et al, 2018(Vogt et al, , 2019. Recognition of the various factors that influence MDR definitions has resulted in recent efforts to develop a standard definition of MDR that is internationally recognized, in order to facilitate comparisons between studies (Magiorakos et al, 2012).…”
Section: Defining Prevalence Outcomes and Prevalence Estimate Parametersmentioning
confidence: 99%
“…Furthermore, a recent study highlights the importance of these different MDR classification metrics; changes in the metric alone produced changes in prevalence values (MacKinnon et al ., 2018). In the relevant wild bird literature, some studies utilized resistance to individual drugs as a metric (Guenther et al ., 2010; Shobrak and Abo-Amer, 2014; Carroll et al , 2015; Pinto et al ., 2015; Vidal et al ., 2017), while others utilized drug classes (Jurado-Tarifa et al ., 2016; Moré et al ., 2017; Thapaliya et al ., 2017). Another important feature of MDR definitions concerns the minimum number of individual drugs, drug classes, or drug categories required for an isolate to be considered multi-drug resistant.…”
Section: Epidemiological and Statistical Considerations For The Intermentioning
confidence: 99%